Long‐term, induced expression of Hand2 in peripheral sympathetic neurons ameliorates sarcopenia in geriatric mice. Issue 6 (21st September 2021) - Rodrigues, Anna Carolina Zaia; Messi, María Laura; Wang, Zhong‐Min; Bonilla, Henry Jacob; Freeman, Willard M.; Delbono, Osvaldo
Abstract: Background: The discovery of adrenoceptors, which mediate the effects of the sympathetic nervous system neurotransmitter norepinephrine on specific tissues, sparked the development of sympathomimetics that have profound influence on skeletal muscle mass. However, chronic administration has serious side effects that preclude their use for muscle‐wasting conditions such as sarcopenia, the age‐dependent decline in muscle mass, force, and power. Devising interventions that can adjust neurotransmitter release to changing physiological demands will require understanding how the sympathetic nervous system affects muscle motor innervation and muscle mass, which will prevent sarcopenia‐associated impaired mobility, falls, institutionalization, co‐morbidity, and premature death. Here, we tested the hypothesis that prolonged heart and neural crest derivative 2 (Hand2) expression in peripheral sympathetic neurons (SNs) ameliorates sympathetic muscle denervation, motor denervation, and sarcopenia in geriatric mice. Methods: We delivered either a viral vector encoding the transcription factor Hand2 or an empty vector (EV) driven to SNs by the PRSx8 promoter by injecting the saphenous vein in 16‐month‐old C57BL/6 mice that were sacrificed 10–11 months later. Studies relied on sympathetic and muscle immunohistochemistry analysed by confocal microscopy, nerve and muscle protein expression assessed by immunoblots, nerve‐evoked and muscle‐evoked maximal muscle contraction force, extensor digitorum longus (EDL) muscle RNA sequencing, SN real‐time PCR, and tests of physical performance using an inverted‐cling grip test and in an open‐arena setting. Results: Examining the mice 10–11 months later, we found that inducing Hand2 expression in peripheral SNs preserved (i) the number of neurons (EV: 0.32 ± 0.03/μm 2, n = 6; Hand2: 0.92 ± 0.08/μm 2, n = 7; P < 0.0001) and size (EV: 279 ± 18 μm 2, n = 6; Hand2: 396 ± 18 μm 2, n = 7; P < 0.0001); (ii) lumbricalis muscle sympathetic innervation (EV: 1.4 ± 1.5 μm/μm 2, n = 5; Hand2: 12 ± 1.8 μm/μm 2, n = 5; P < 0.001); (iii) tibialis anterior, gastrocnemius, EDL, and soleus muscles weight and whole‐body strength (EV: 48 ± 6.4 s, n = 6; Hand2: 102 ± 6.8 s, n = 6; P < 0.001); (iv) EDL type IIb, IIx, and II/IIx and soleus type I, IIa, IIx, IIa/IIx, and IIb/IIx myofibre cross‐sectional area; (v) nerve‐evoked (EV: 16 ± 2.7 mN; Hand2: 30 ± 4.4 mN; P < 0.001) and muscle‐evoked (EV: 24 ± 3.8 mN, n = 5; Hand2: 38 ± 3.0 mN, n = 8; P < 0.001) muscle force by 150 Hz–3 s pulses; and (vi) motor innervation assessed by measuring presynaptic/postsynaptic neuromuscular junction area overlay. Conclusions: Preserving Hand2 expression in SNs from middle‐aged to very old mice attenuates decreases in muscle mass and force by (i) maintaining skeletal muscle sympathetic and motor innervation, (ii) improving membrane and total acetylcholine receptor stability and nerve‐evoked and muscle‐evoked muscle contraction, (iii) preventing the elevation of inflammation and myofibrillar protein degradation markers, and (iv) increasing muscle autophagy.